Деякі питання публічного адміністрування суб’єктів сектору безпеки України - Цибульник, Н. Ю.; Tsybulnyk, N. Yu. (Прикарпатський юридичний вісник. - 2022. - Вип. 6 (47). - С. 115-119, 2022)
Визначено поняття сектору безпеки та його суб’єктів. Установлено ознаки та види публічного адміністрування сектору безпеки України. Акцентовано увагу на необхідності розробки у сфері публічного адміністрування сектору безпеки України нового законодавчого регулювання стосовно розвитку воєнної, державної, економічної, громадської‚ інформаційної, екологічної, кібербезпеки‚ енергетичної безпеки, яке б визначило шляхи й інструменти її реалізації‚ було спрямовано на протидію наявним і прогнозованим загрозам національній безпеці та національним інтересам України. Вказано на значення сектору безпеки України як однієї із складових держави. Виділено провідну роль суб’єктів публічно-правової діяльності у забезпеченні національної безпеки.

The article is devoted to defining the concept of the security sector and its subjects. The article states that to ensure national security, it is necessary to organize social relations, carry out effective preventive activities, and warn against various threats. Signs and types of public administration of the security sector of Ukraine have been established. Attention was focused on the need to develop in the sphere of public administration of the security sector of Ukraine a new legislative regulation regarding the development of military, state, economic, public, information, environmental, cyber security, energy security, which would determine the ways and tools of its implementation, was aimed at counteracting existing and projected threats to national security and national interests of Ukraine. The conclusions indicate the importance of the security and defense sector of Ukraine as one of the components of the state. The leading role of subjects of public and legal activity in ensuring national security is highlighted. In connection with recent events related to state development and changes in political courses, high-quality provision of administrative and legal regulation of all spheres is very important. The mechanism for ensuring national security is an appropriate set of legal means that regulate social relations and play a preventive role, warning of various types of threats. It is worth noting that the control and orderliness of social relations consists in ensuring social balance. That is, the existence of a balance between private and public interest, which primarily depends on the system of legal means, is important. Accordingly, public administration is a unique tool for achieving balance. In turn, effective public administration of the security sector, which requires systematization and clear legislative regulation, should ensure quality work and effectiveness. In addition, it is worth paying attention to the fact that this direction of regulation of social relations is quite relevant considering the social system that exists now.

Определено понятие сектора безопасности и его субъектов. Установлены признаки и виды публичного администрирования сектора безопасности Украины. Акцентировано внимание на необходимости разработки в сфере публичного администрирования сектора безопасности Украины нового законодательного регулирования относительно развития военной, государственной, экономической, общественной, информационной, экологической, кибербезопасности, энергетической безопасности, которое бы определило пути и инструменты ее реализации, было направлено на противодействие имеющимся и прогнозируемым угрозам национальной безопасности и интересам Украины. Указано значение сектора безопасности Украины как одной из составляющих государства. Выделена ведущая роль субъектов публично-правовой деятельности в обеспечении национальной безопасности.
Some issues of public administration of subjects of the security sector of Ukraine
Цибульник, Н. Ю. Деякі питання публічного адміністрування суб’єктів сектору безпеки України / Н. Ю. Цибульник // Прикарпатський юридичний вісник. - 2022. - Вип. 6 (47). - С. 115-119. - DOI: https://doi.org/10.32782/pyuv.v6.2022.23.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; сектор безпеки; security sector; сектор безопасности; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование; публічне адміністрування; public administration; публичное администрирование; суб’єкти сектору безпеки України; subjects of the security sector of Ukraine; субъекты сектора безопасности Украины